Improving Architectural Drawing Students' Achievement by Coalescing Computer-Aided Design with the Compass Method - Oladiran Stephen Olabiyi (INVOTEC, 2022)
This study combined computer-aided design with compass approaches, employing quasi-experimental design pre-test, post-test, and a non-equivalent control group, to improve the cognitive performance of architectural drawing students. The  study addressed three objectives and investigated three null hypotheses. Thestudy's target audience was 125 senior secondary year two architectural drawing students. The experimental group received ten weeks of training using the marker board compass approach, while the control group received ten weeks of instruction using computer-aided design. Data was collected using the Architectural Drawing Achievement Test, which has a reliability rate of 0.86 using Kuder-Richardson 21. Three experts validated the test's face and content. The results revealed that the experimental group's students performed more effectively at architectural drawing than those in the control group. The cognitive achievement of students is significantly influenced by gender, favouring males. Additionally, in the area of architectural drawing, high-achievers students outperformed lowachievers students by barely. Based on these results, it was suggested that senior secondary schools in Nigeria teach architectural drawing using a combination of computer-aided design and the compass method.